Analisis Efektivitas Penerimaan Pajak dan Retribusi pada Pendapatan Asli Daerah di Kabupaten Tegal Tahun 2014-2018 - Ekaputra, Aditiyanto (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Local revenue is one of the sources of regional finance that can be utilized to organize regional autonomy optimally. This study aims to examine the effectiveness of the performance of local tax revenue and levies on local revenue of Tegal Regency in 2014-2018. The method used is quantitative descriptive with data from regional retribution studies. The results of the study show that the level of effectiveness in local revenue has an average value of 102.89% (very effective). While the level of effectiveness of local taxes has an average value of 101.86% (very effective). Then for the effectiveness of levies has an average value of 90.04% (effective).